Attenuation and transport of human enteric viruses and bacteriophage MS2 in alluvial sand and gravel aquifer media—laboratory studies. (15th May 2021) - Pang, Liping; Farkas, Kata; Lin, Susan; Hewitt, Joanne; Premaratne, Aruni; Close, Murray
Highlights: Norovirus removal was somewhat lower than MS2 removal in alluvial sand. Filtration removal in alluvial gravel was MS2 < adenovirus < rotavirus. Virus detachment favours free virus transport and poses a groundwater quality risk. More studies are needed to compare surrogates with pathogens, especially norovirus. Abstract: Potable groundwater contamination by human enteric viruses poses serious health risks. Our understanding of virus subsurface transport has largely depended on studying bacteriophages as surrogates. Few studies have compared the transport behaviour of enteric viruses, especially norovirus, with phage surrogates. We conducted laboratory column experiments to investigate norovirus and bacteriophage MS2 (MS2) filtration in alluvial sand, and rotavirus, adenovirus and MS2 filtration in alluvial gravel aquifer media in 2 mM NaCl (pH 6.6–6.9) with pore velocities of 4.6–5.4 m/day. The data were analysed using colloid filtration theory and HYDRUS-1D 2-site attachment-detachment modelling. Norovirus removal was somewhat lower than MS2 removal in alluvial sand. The removal of rotavirus and adenovirus was markedly greater than MS2 removal in alluvial gravel. These findings concurred with the log10 reduction values, mass recoveries, attachment efficiencies and irreversible deposition rate constants. The modelling results suggested that the MS2 detachment rates were in the same order of magnitude as norovirus, but they were 1 order of magnitude faster than those of rotavirus and adenovirus. The attachment of viruses and MS2 was largely reversible with faster detachment than attachment rates, favouring free virus transport. These findings highlight the risk associated with continual virus transport through subsurface media if viruses are not inactivated and remobilising previously attached viruses could trigger contamination events. Thus, virus attachment reversibility should be considered in virus transport predictions in subsurface media. Further research is needed to compare surrogates with enteric viruses, especially norovirus, regarding their transport behaviours under different experimental conditions. Graphical abstract: Image, graphical abstract